The Coming Hypersonic Era - Peter J. McLaughlin (Journal Of Global Strategic Studies, 2023)
Much of the literature on emerging hypersonic weapons discusses their ability to deliver strategic nuclear strikes, conduct nuclear counterforce, or perform traditional tactical strikes in isolation. However, with their inherent versatility, a single hypersonic weapon can perform all of these roles without reconfiguration. I explain how the versatility of these new multipurpose weapons generates ambiguity and undermines the tenets of nuclear deterrence theory. National leaders who observe HPGM deployments on their nations’ borders will increasingly view HPGM weapons as tools of destabilizing counterforce, even if the deployers have defensive intentions. With HPGMs capable of traveling inter-continental distances on the horizon, policies of restraint will become necessary to clearly indicate intentions without increasing global fear of counterforce strikes.